2006
DOI: 10.1213/01.ane.0000194300.56739.1a
|View full text |Cite
|
Sign up to set email alerts
|

The Size 1½ ProSeal™ Laryngeal Mask Airway in Infants: A Randomized, Crossover Investigation with the Classic™ Laryngeal Mask Airway

Abstract: Many problems with the Classic laryngeal mask airway (CLMA) in infants are believed to be related to its inadequate cuff design. One of the main limitations of the CLMA is that the resulting low-pressure seal can be inadequate for positive pressure ventilation (PPV). The ProSeal LMA (PLMA), a new laryngeal mask airway with a modified cuff, has been shown to form a more effective seal than the CLMA in children. The first infant size PLMA, size 1(1/2), became available recently. We studied 30 anesthetized, nonpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
73
5
4

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(98 citation statements)
references
References 27 publications
16
73
5
4
Order By: Relevance
“…Our data on neutral OLP values and, commensurately, our V T max values for the air-Q ILA are lower than existing published data for the PLMA. [2][3][4]14 Our findings for air-Q ILA sizes 1.5 and 2.0 are similar to those previously published, 10,11 where the mean (standard deviation [SD]) OLP was 17.5 (6.4) cm H 2 O and 18.5 (1.6) cm H 2 O for size 1.5 and 15.7 (4.3) cm H 2 O for size 2.0. Our OLP findings for size 1 were higher than those by Sinha et al 11 who reported a mean (SD) OLP of 18.5 (2.1) cm H 2 O. Oropharyngeal leak pressures increase when the patient's neck is in the flexed position, a phenomenon also described with the PLMA.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our data on neutral OLP values and, commensurately, our V T max values for the air-Q ILA are lower than existing published data for the PLMA. [2][3][4]14 Our findings for air-Q ILA sizes 1.5 and 2.0 are similar to those previously published, 10,11 where the mean (standard deviation [SD]) OLP was 17.5 (6.4) cm H 2 O and 18.5 (1.6) cm H 2 O for size 1.5 and 15.7 (4.3) cm H 2 O for size 2.0. Our OLP findings for size 1 were higher than those by Sinha et al 11 who reported a mean (SD) OLP of 18.5 (2.1) cm H 2 O. Oropharyngeal leak pressures increase when the patient's neck is in the flexed position, a phenomenon also described with the PLMA.…”
Section: Discussionsupporting
confidence: 90%
“…Previously published studies of performance of new iterations of LMAs in adults and children have used similar group sizes. [2][3][4] Data are described with median [P25,P75] for continuous data and frequency (percent) for discrete and categorical data. Due to its observational design, this study was not powered for comparisons, and as such, no inferential methods of statistical analysis were employed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shimbori et al 18 performed a randomized, non-blinded study in 19 showed a difference in leak pressure between groups (PLMA 33 cm H 2 O; CLMA 26 cm H 2 O), as well as a higher incidence of gastric insufflation with the CLMA, with no difference in fibreoptic view. These mean leak pressures far exceed those observed in the studies previously described [15][16][17][18] as well as the current investigation. The inclusion of the size 3 PLMA, which has a posterior cuff, may account for the higher mean leak pressures observed, as well as compromisation of the fibreoptic view as seen in adult studies.…”
Section: Discussioncontrasting
confidence: 61%
“…Randomized crossover studies of the PLMA vs CLMA sizes 1 ½, 15 2 16 and 2 ½ 17 have been published by Goldmann et al [15][16][17] In these studies, with the patient's head in the neutral position, the OPL by auscultation was higher for the PLMA (size 2 PLMA -18.8 cm H 2 O; size 2 CLMA -15.0 cm H 2 O). Gastric insufflation was more common for the CLMA and was absent for the PLMA.…”
Section: Discussionmentioning
confidence: 99%